Microbial Spoilage and Preservation of Wine: Using Weapons from Nature’s Own Arsenal -A Review - du Toit, M.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2019)
The winemaking process includes multiple stages at which microbial spoilage can occur, altering the quality and hygienic status of the wine and rendering it unacceptable. The major spoilage organisms include species and strains of the yeast genera Brettanomyces, Candida, Hanseniaspora, Pichia, Zygosaccharomyces etc., the lactic acid bacterial genera Lactobacillus, Leuconostoc, Pediococcus, etc. and the acetic acid bacterial genera Acetobacter and Gluconobacter. The faults caused include bitterness and off.flavours (mousiness, ester taint, phenolic, vinegary, buttery, geranium tone), and cosmetic problems such as turbidity, viscosity, sediment and film formation. These spoilage organisms can also affect the wholesomeness of wine by producing biogenic amines and precursors of ethyl carbamate. The judicious use of chemical preservatives such as sulphur dioxide (S02) during the winemaking process decreases the risk of microbial spoilage, but strains vary considerably in their S02 sensitivity. There is, moreover, mounting consumer bias against chemical preservatives, and this review focuses on the possible use of biopreservatives in complying with the consumers’ demand for "clean and green" products.